Implementasi Peraturan Mentri Pendidikan, Kebudayaan, Riset, Dan Teknologi Nomor 30 Tahun 2021 Tentang Pencegahan Dan Penanganan Kekerasan Seksual: Melalui Studi di Universitas Bandar Lampung (International Forum of Researchers and Lecturers, 2024)
This scientific article aims to determine the implementation of Minister of Education, Culture, Research and Technology Regulation Number 30 of 2021 concerning Prevention and Handling of Sexual Violence in Higher Education Environments, factors inhibiting the implementation of Minister of Education, Culture, Research and Technology Regulation Number 30 of 2021 concerning Prevention and to find out how the realization of the formation of an anti-sexual violence task force, (Study at Bandar Lampung University), the efforts made by universities in realizing the Minister of Education, Culture, Technology and Research Regulation N0.30 of 2021 concerning Prevention and Handling of Sexual Violence on Campus Sexual Violence (Study at Bandar Lampung University). The research method in writing this scientific article uses empirical juridical methods. The results of the research show that the formation of an anti-sexual violence task force has not yet been fully realized because the Ministry of Education and Culture is still designing the scheme and mechanism for its formation. The formation of a task force must be realized immediately to prevent ongoing sexual violence and provide information on the importance of efforts that must be taken to prevent sexual violence from occurring.